2023
DOI: 10.1128/spectrum.02825-23
|View full text |Cite
|
Sign up to set email alerts
|

Microbisporicin (NAI-107) protects Galleria mellonella from infection with Neisseria gonorrhoeae

Nele Hofkens,
Zina Gestels,
Said Abdellati
et al.

Abstract: Due to the increasing incidence of antibiotic-resistant bacterial pathogens, the need for the development of alternative compounds is of utmost importance. Bacteriocins are considered a promising alternative to antibiotics. In this study, we determined the in vitro activities of 65 bacteriocins from the PARAGEN collection along with microbisporicin (NAI-107) against 14 WHO reference isolates of Neisseria gonorrhoeae , one isolate of Neisseria meningit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…We did not evaluate N. gonorrhoeae WHO N (which had the highest ramoplanin MIC) in the in vivo model. Our choice of N. gonorrhoeae WHO P was based on previous studies in our laboratory that established that this strain can be successfully used to evaluate novel therapeutic agents for the treatment of N. gonorrhoeae [18]. Other studies have found evidence of synergy between ramoplanin and the lantibiotic actagardine for C. difficile [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We did not evaluate N. gonorrhoeae WHO N (which had the highest ramoplanin MIC) in the in vivo model. Our choice of N. gonorrhoeae WHO P was based on previous studies in our laboratory that established that this strain can be successfully used to evaluate novel therapeutic agents for the treatment of N. gonorrhoeae [18]. Other studies have found evidence of synergy between ramoplanin and the lantibiotic actagardine for C. difficile [10].…”
Section: Discussionmentioning
confidence: 99%
“…gonorrhoeae WHO P was based on previous studies in our laboratory that established that this strain can be successfully used to evaluate novel therapeutic agents for the treatment of N. gonorrhoeae [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations